Recycling Infrastructure in Cambodia Circularity, Waste, and Urban Life in Phnom Penh (Taylor & Francis, 2023)
socially marginalized, waste pickers, recycling, infrastructure, urban life, labor autonomy, environmental
English
Keywords: Ethnic studies; Regional / International studies; socially marginalized, waste pickers, recycling, infrastructure, urban life, labor autonomy, environmental